2010
DOI: 10.1002/aenm.201000009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Partially Graphitic Ordered Mesoporous Carbons with High Surface Areas

Abstract: Graphitic carbons with ordered mesostructure and high surface areas (of great interest in applications such as energy storage) have been synthesized by a direct triblock‐copolymer‐templating method. Pluronic F127 is used as a structure‐directing agent, with a low‐molecular‐weight phenolic resol as a carbon source, ferric oxide as a catalyst, and silica as an additive. Inorganic oxides can be completely eliminated from the carbon. Small‐angle XRD and N2 sorption analysis show that the resultant carbon materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
120
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(128 citation statements)
references
References 51 publications
(48 reference statements)
6
120
0
2
Order By: Relevance
“…Then the OMC was synthesized via the EISA process with some minor modifications by our group (Gao et al, 2011). Typically, 1.6 g F127 was dissolved in 6.0 g ethanol at 313 K, then 5.0 g resol solution was added to form mixture A.…”
Section: Synthesis Of Materialsmentioning
confidence: 99%
“…Then the OMC was synthesized via the EISA process with some minor modifications by our group (Gao et al, 2011). Typically, 1.6 g F127 was dissolved in 6.0 g ethanol at 313 K, then 5.0 g resol solution was added to form mixture A.…”
Section: Synthesis Of Materialsmentioning
confidence: 99%
“…Wang et al reported a co-gelation route to synthesize porous graphitized carbons by using teraethylorthosilicate (TEOS) as a template, metal nitrates as catalyst and furfuryl alcohol (FA) as precursor [19]. Gao et al synthesized graphitized carbons with an ordered mesoporous structure using ferric oxide as catalyst, which can even achieve a specific capacitance of 155 F g À1 at a scan rate of 200 mV s À1 [20]. Sevilla et al obtained graphitized porous carbons by catalytic graphitization of porous carbons with silica xerogel as a template and phenolic resin as carbon precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Although the theoretical results seem to be exciting, not much experimental works have been done in this regard due to the lack of proper fabrication techniques to incorporate metal atoms within the graphene network to give required H 2 binding energy [4], and hence, deserve much attention. Also, the recent advancements in the fabrication of partially graphitic micro/mesoporous carbon has shown improved hydrogen uptake capacity due to the high surface area into the porous structure and favorable hydrogen binding energy in the local curvature of graphene sheets in the short-range graphitic structures [1,3,13]. Therefore a metal-incorporated partially graphitic porous carbon network containing few-layer graphene may potentially improve the hydrogen storage capacity to achieve the elusive DOE goal.…”
Section: Introductionmentioning
confidence: 97%